Teaching note: Consulting Higher Education in Africa - A Strategic Case Study - Brice, David; Katzenstein, James; Norman, Thomas J. (Senate Hall, 2019)
While some would think the focus might be on this specific African college and its unique situational outcomes, the central focus of this paper is the development and implementation of a consulting model, the Katzenstein Inter-Culture Consulting Model (KICM), that provides for an equal relationship, and allows for cultural relevance, between a rich US college that is transferring capability, and a poor Ethiopian college that wishes to upgrade its administration and pedagogy. As this is a real-world case, the ultimate outcome is still very much in the future but here we have discussed the process.
Keywords: Africa|entrepreneurship|business education|developing economy|educational entrepreneurship|transferring capability